By Necessity or by Right: The Language and Experience of Gender at Work - Christie, Nancy (Labour/Le Travailleur, 2002)
Abstract This article reviews the contribution that Labour/Le Travail has made to the study of gender history in Canada over the past 25 years. It identifies the several ways in which industrialization led to gendering of class, and in particular analyzes the contribution of the patriarchy/capitalism debate, the family strategies approach, and the new literature on masculinity. It suggests the need for more broadly contextualized studies that incorporate both gender conflict and interdependence, and argues for a hermeneutic separation of gender and class identities from conceptualizations of class politics and collective protest.